A Comparative Survey on Symmetric Key Encryption Techniques - CH Venkata Navi,P.Sandeep Reddy,Md Ayub Khan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Nowadays, the use of internet are growing increasingly across the world, security becomes a prime concern of issue for the society. Earlier security was a major issue for military applications but now the area of applications has been enhanced since most of the communication takes place over the web. Cryptography is an area of computer science which is developed to provide security for the senders and receivers to transmit and receive confidential data through an insecure channel by a means of process called Encryption/ Decryption. Cryptography ensures that the message should be sent without any alterations and only the authorized person can be able to open and read the message. A number of cryptographic techniques are developed for achieving secure communication. There are basically two techniques of cryptography- Symmetric and Asymmetric. This paper presents a detailed study of most of the symmetric encryption techniques with their advantages and limitations over each other.